Provocation and Motivation: A Response to Dr. Brian Patrick Green, “Emerging Technologies as Provocations for Theology and Ethics” - Moon, Catherine (Theology and science, 2026)
The provocations of artificial intelligence and emerging technologies demand earnest reflection not only on how humans should ethically respond to these provocations but also demands earnest reflection on the nature of these provocations themselves. What is provocation? Do the provocations of artificial intelligence and emerging technology differ from other kinds of provocations? This response considers these questions in light of St. Edith Stein’s philosophy of motivation. By connecting the idea of technological provocation to motivation, it ultimately suggests that the lawfulness of meaning provokes or motivates the soul to freely respond to the inherent meaning and value of what is encountered in experience. The very fact of provocation directs us toward the inherent lawfulness and meaningful structures of reality but individual provocations can always work against this lawfulness and directs to act against the meaningful structures of reality or worse impel us to not be provoked but what we encounter at all.